Zirconium chloride lithium solid electrolyte and preparation method thereof
By colliding with gaseous lithium chloride and zirconium chloride under a vacuum sealed environment, the problem of long reaction time and uniformity in the existing technology is solved, and the efficient preparation of lithium zirconium chloride is achieved and its electricity is improved. Chemical properties.
Patent Information
- Application Number
- CN202411206542.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
There are problems in the existing zirconium chloride synthesis technology that have long reaction time and difficult to ensure uniformity of reaction.
The gaseous lithium chloride and gaseous zirconium chloride collide in a vacuum sealed environment. After the reaction is finished, the solid electrolyte of zirconium chloride is obtained. The gasification temperature of the material is reduced by reducing the pressure, and the reaction efficiency and product uniformity are improved. .
The resulting lithium zirconium chloride has higher powder uniformity, excellent surfactivity, better product stability and better electrochemical performance.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolyte preparation, and in particular to a lithium zirconium chloride solid electrolyte and a preparation method thereof. Background Art
[0002] All-solid-state battery technology fundamentally avoids the introduction and use of organic liquid electrolytes, effectively ensuring its intrinsic safety in terms of material composition; at the same time, the thermodynamic stability of solid inorganic compounds allows the selection of positive and negative electrode materials to be expanded to material systems with high specific capacity or high working potential, thereby greatly improving the energy density of the battery, and is becoming an important development direction for the next generation of lithium batteries.
[0003] As an emerging material system, metal chloride solid electrolytes have both the antioxidant properties of oxide solid electrolytes and the high ionic conductivity and mechanical ductility of sulfide solid electrolytes. The preparation process is simple, and does not require harsh environments and extremely high sintering temperatures. They have great potential for large-scale production and are gradually becoming one of the competitors for the technical route to achieve the commercialization of all-solid-state batteries.
[0004] Metal chloride-based solid electrolyte materials have unique anionic chemical properties, taking into account the performance advantages of metal oxides and metal sulfides, and achieving an ideal balance between good interface stability and ionic conductivity. Therefore, metal chlorides are regarded as a type of solid electrolyte material system with excellent comprehensive performance and development potential. At present, the existing lithium zirconium chloride synthesis technologies mainly include high-energy ball milling, gaseous zirconium chloride and liquid lithium chloride interfacial reaction synthesis, etc. For example, the Chinese invention patent with application number 202010972122.2 discloses a method for preparing lithium zirconium chloride, in which zirconium tetrachloride and lithium chloride are ball-milled and pressed according to a certain mass ratio to obtain lithium zirconium chloride. For the above technical routes, there are problems such as long reaction time and difficulty in ensuring reaction uniformity. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a lithium zirconium chloride solid electrolyte with good reaction uniformity and a preparation method thereof.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a lithium zirconium chloride solid electrolyte, comprising the following steps: gaseous lithium chloride and gaseous zirconium chloride collide with each other, and after the reaction is completed, cooling to obtain a lithium zirconium chloride solid electrolyte.
[0007] The technical solution adopted by the present invention is: a lithium zirconium chloride solid electrolyte prepared by the above preparation method.
[0008] The beneficial effect of the present invention is that the preparation method of the lithium zirconium chloride solid electrolyte of the present invention adopts the reaction of gaseous zirconium tetrachloride and gaseous lithium chloride to form lithium zirconium chloride with higher powder uniformity, excellent surface activity and better quality stability, thereby improving the electrochemical performance of lithium zirconium chloride. DETAILED DESCRIPTION
[0009] In order to explain the technical content, achieved objectives and effects of the present invention in detail, the following is an explanation in conjunction with the implementation modes.
[0010] A method for preparing a lithium zirconium chloride solid electrolyte comprises the following steps: gaseous lithium chloride and gaseous zirconium chloride collide with each other and after the reaction is completed, cool the reaction to obtain the lithium zirconium chloride solid electrolyte.
[0011] From the above description, it can be seen that the beneficial effects of the present invention are: the preparation method of the lithium zirconium chloride solid electrolyte provided by the present invention adopts gaseous zirconium tetrachloride and gaseous lithium chloride for collision reaction. Compared with ball milling mixing and gas-liquid interface reaction, gaseous zirconium tetrachloride and gaseous lithium chloride can be perfectly mixed and fused, the reaction rate is fast, the reaction is efficient and sufficient, the generated lithium zirconium chloride has better uniformity, high surface activity, better product stability, and better electrochemical performance.
[0012] Furthermore, the preparation method of gaseous lithium chloride comprises the following steps: placing solid lithium chloride in a first closed reactor, evacuating to a vacuum degree of ≤10Pa, then heating to 1350-1400°C, and keeping the temperature for 2-5h to obtain gaseous lithium chloride.
[0013] From the above description, it can be seen that the present invention adopts reduced pressure to reduce the gasification temperature of the material, which can not only reduce energy consumption and reaction conditions, but also reduce the impact of air in the environment on the performance of the electrolyte.
[0014] Furthermore, the heating rate to 1350-1400° C. is 1-3° C. / min.
[0015] From the above description, it can be seen that the present invention adopts a lower heating rate to avoid damage to the equipment.
[0016] Furthermore, the preparation method of gaseous zirconium chloride includes the following steps: placing solid zirconium tetrachloride in a second closed reactor, evacuating to a vacuum degree of ≤10Pa, heating to 335-415°C, and keeping warm for 1-3h to obtain gaseous zirconium tetrachloride.
[0017] From the above description, it can be seen that the present invention adopts reduced pressure to reduce the gasification temperature of the material, which can not only reduce energy consumption and reaction conditions, but also reduce the impact of air in the environment on the performance of the electrolyte.
[0018] Furthermore, the heating rate to 335-415° C. is 1-2.2° C. / min.
[0019] Furthermore, the collision reaction is carried out in a third closed reactor, and before the gaseous lithium chloride and gaseous zirconium chloride are introduced, the third closed reactor is first evacuated to ≤10 Pa.
[0020] From the above description, it can be seen that the third closed reactor is evacuated to ≤10Pa, which can reduce the influence of air in the environment on the performance of the electrolyte.
[0021] Furthermore, the first closed reactor, the second closed reactor and the third closed reactor are all ceramic reactors lined with corrosion-resistant alloy.
[0022] From the above description, it can be seen that the ceramic reactor with corrosion-resistant alloy lining can meet the requirements of high-temperature fluidized bed reaction.
[0023] Furthermore, the purity of lithium chloride and zirconium tetrachloride is ≥98%.
[0024] It can be seen from the above description that the purity of lithium chloride and zirconium tetrachloride is limited to reduce the impact of impurities on the solid electrolyte.
[0025] Furthermore, the molar ratio of lithium chloride to zirconium tetrachloride in the collision reaction is 1.16-1.22:1.
[0026] From the above description, it can be seen that the content of lithium chloride in the collision reaction is designed to be excessive to ensure that the amount of lithium ions is sufficient after the lithium is volatilized and lost in the subsequent battery manufacturing process.
[0027] Furthermore, the method also includes the step of grinding the lithium zirconium chloride solid electrolyte into powder, wherein the grinding is performed in a dry inert atmosphere.
[0028] The technical solution adopted by the present invention is: a lithium zirconium chloride solid electrolyte prepared by the above preparation method.
[0029] Furthermore, the chemical formula of lithium zirconium chloride is Li x ZrCl 5+x , where x<1.
[0030] Embodiment 1 of the present invention is: a lithium zirconium chloride solid electrolyte, the steps are as follows:
[0031] The purity of lithium chloride and zirconium tetrachloride is ≥98%. Solid lithium chloride and zirconium tetrachloride are weighed in a drying room at a molar ratio of 1.16:1 and added to the first closed reactor and the second closed reactor respectively. The sealing device is locked, and the mechanical pump + Roots pump is turned on to pump to a vacuum degree of 10Pa in the first closed reactor and a vacuum degree of 7Pa in the second closed reactor; the first closed reactor is continuously heated to 1370℃ at 1.5℃ / min and kept warm for 2.0h; the second closed reactor is continuously heated to 343℃ at 2℃ / min and kept warm for 1h. Simultaneously, the third closed reactor is evacuated to 5pa. The control connecting valves on the connecting pipes of the first closed reactor and the second closed reactor to the third closed reactor are opened respectively, and the gaseous lithium chloride in the first closed reactor and the gaseous zirconium tetrachloride in the second closed reactor are synchronously introduced into the third closed reactor, and the gaseous lithium chloride and the gaseous zirconium chloride in the third closed reactor collide and react. After the reaction is completed, the solid particles of lithium zirconium chloride are obtained by cooling, and then ultrafine grinding is performed in a dry inert atmosphere to obtain solid lithium zirconium chloride electrolyte powder. The first closed reactor, the second closed reactor and the third closed reactor are all ceramic reactors lined with corrosion-resistant alloy.
[0032] By pressing into electrolyte sheets, the average ionic conductivity of the material was detected at room temperature to be 4.56×10 -3 S / cm, indicating that the electrolyte exhibits excellent electrochemical performance at room temperature.
[0033] Embodiment 2 of the present invention is: a lithium zirconium chloride solid electrolyte, the steps are as follows:
[0034] The purity of lithium chloride and zirconium tetrachloride is ≥98%. Solid lithium chloride and zirconium tetrachloride are weighed in a drying room at a molar ratio of 1.18:1 and added to the first closed reactor and the second closed reactor respectively. The sealing device is locked, and the mechanical pump + Roots pump is turned on to pump to a vacuum degree of 6Pa in the first closed reactor and a vacuum degree of 6Pa in the second closed reactor; the first closed reactor is continuously heated to 1387℃ at 2℃ / min and kept warm for 2.5h; the second closed reactor is continuously heated to 352℃ at 1.0℃ / min and kept warm for 1.5h. Simultaneously, the third closed reactor is evacuated to 6pa. The control connecting valves on the connecting pipes of the first closed reactor and the second closed reactor to the third closed reactor are opened respectively, and the gaseous lithium chloride in the first closed reactor and the gaseous zirconium tetrachloride in the second closed reactor are synchronously introduced into the third closed reactor, and the gaseous lithium chloride and the gaseous zirconium chloride in the third closed reactor collide and react. After the reaction is completed, the solid particles of lithium zirconium chloride are obtained by cooling, and then ultrafine grinding is performed in a dry inert atmosphere to obtain solid lithium zirconium chloride electrolyte powder. The first closed reactor, the second closed reactor and the third closed reactor are all ceramic reactors lined with corrosion-resistant alloy.
[0035] By pressing into electrolyte sheets, the average ionic conductivity of the material was detected at room temperature to be 5.41×10 -3 S / cm, indicating that the electrolyte exhibits excellent electrochemical performance at room temperature.
[0036] Embodiment 3 of the present invention is: a lithium zirconium chloride solid electrolyte, the steps are as follows:
[0037] The purity of lithium chloride and zirconium tetrachloride is ≥98%. Solid lithium chloride and zirconium tetrachloride are weighed in a drying room at a molar ratio of 1.22:1 and added to the first closed reactor and the second closed reactor respectively. The sealing device is locked, and the mechanical pump + Roots pump is turned on to pump to a vacuum degree of 5Pa in the first closed reactor and a vacuum degree of 5Pa in the second closed reactor; the first closed reactor is continuously heated to 1390℃ at 1.2℃ / mim and kept warm for 3.0h; the second closed reactor is continuously heated to 395℃ at 1.0℃ / mim and kept warm for 1.2h. Simultaneously, the third closed reactor is evacuated to 5pa. The control connecting valves on the connecting pipes of the first closed reactor and the second closed reactor to the third closed reactor are opened respectively, and the gaseous lithium chloride in the first closed reactor and the gaseous zirconium tetrachloride in the second closed reactor are synchronously introduced into the third closed reactor, and the gaseous lithium chloride and the gaseous zirconium chloride in the third closed reactor collide and react. After the reaction is completed, the solid particles of lithium zirconium chloride are obtained by cooling, and then ultrafine grinding is performed in a dry inert atmosphere to obtain solid lithium zirconium chloride electrolyte powder. The first closed reactor, the second closed reactor and the third closed reactor are all ceramic reactors lined with corrosion-resistant alloy.
[0038] By pressing into electrolyte sheets, the average ionic conductivity of the material was detected at room temperature to be 5.22×10 -3 S / cm, indicating that the electrolyte exhibits excellent electrochemical performance at room temperature.
[0039] Embodiment 4 of the present invention is: a lithium zirconium chloride solid electrolyte, the steps are as follows:
[0040] The purity of lithium chloride and zirconium tetrachloride is ≥98%. Solid lithium chloride and zirconium tetrachloride are weighed in a drying room at a molar ratio of 1.20:1 and added to the first closed reactor and the second closed reactor respectively. The sealing device is locked, and the mechanical pump + Roots pump is turned on to pump to a vacuum degree of 3Pa in the first closed reactor and a vacuum degree of 5Pa in the second closed reactor; the first closed reactor is continuously heated to 1400℃ at 2.6℃ / mim and kept warm for 2.5h; the second closed reactor is continuously heated to 381℃ at 2.20℃ / mim and kept warm for 2h. Simultaneously, the third closed reactor is evacuated to 5pa. The control connecting valves on the connecting pipes of the first closed reactor and the second closed reactor to the third closed reactor are opened respectively, and the gaseous lithium chloride in the first closed reactor and the gaseous zirconium tetrachloride in the second closed reactor are synchronously introduced into the third closed reactor, and the gaseous lithium chloride and the gaseous zirconium chloride in the third closed reactor collide and react. After the reaction is completed, the solid particles of lithium zirconium chloride are obtained by cooling, and then ultrafine grinding is performed in a dry inert atmosphere to obtain solid lithium zirconium chloride electrolyte powder. The first closed reactor, the second closed reactor and the third closed reactor are all ceramic reactors lined with corrosion-resistant alloy.
[0041] By pressing into electrolyte sheets, the average ionic conductivity of the material was detected at room temperature to be 5.09×10 -3 S / cm, indicating that the electrolyte exhibits excellent electrochemical performance at room temperature.
[0042] Embodiment 5 of the present invention is: a lithium zirconium chloride solid electrolyte prepared by the preparation method of embodiment 1, wherein the chemical formula of lithium zirconium chloride is Li1ZrCl6.
[0043] In summary, the lithium zirconium chloride solid electrolyte and its preparation method provided by the present invention contact gaseous lithium chloride with gaseous zirconium tetrachloride in a dry vacuum sealed environment, react to generate lithium zirconium chloride, and obtain solid electrolyte lithium zirconium chloride after cooling. The gaseous reactants can be perfectly mixed and fused, the reaction rate is fast, the reaction is efficient and sufficient, the generated lithium zirconium chloride has better uniformity, high surface activity, better product stability, and better electrochemical performance. The use of reduced pressure to reduce the gasification temperature of the material during the reaction process can not only reduce energy consumption and reduce reaction conditions, but also reduce the impact of air in the environment on the performance of the electrolyte.
[0044] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the specification of the present invention, or directly or indirectly applied in related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a lithium zirconium chloride solid electrolyte, characterized in that: The following steps are involved: Gaseous lithium chloride and gaseous zirconium chloride collide and react, and after the reaction is completed, they are cooled to obtain a lithium zirconium chloride solid electrolyte.
2. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 1, characterized in that: The method for preparing gaseous lithium chloride comprises the following steps: placing solid lithium chloride in a first closed reactor, evacuating to a vacuum degree of ≤10Pa, then heating to 1350-1400°C, and keeping the temperature for 2-5h to obtain gaseous lithium chloride.
3. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 2, characterized in that: The heating rate to 1350-1400° C. is 1-3° C. / min.
4. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 1, characterized in that: The method for preparing gaseous zirconium chloride comprises the following steps: placing solid zirconium tetrachloride in a second closed reactor, evacuating to a vacuum degree of ≤10Pa, heating to 335-415°C, and keeping the temperature for 1-3h to obtain gaseous zirconium tetrachloride.
5. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 1, characterized in that: The collision reaction is carried out in a third closed reactor. Before the gaseous lithium chloride and gaseous zirconium chloride are introduced, the third closed reactor is first evacuated to a pressure of ≤10 Pa.
6. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 1, characterized in that: The purity of the lithium chloride and zirconium tetrachloride are both ≥98%.
7. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 1, characterized in that: The molar ratio of lithium chloride to zirconium tetrachloride in the collision reaction is 1.16-1.22:
1.
8. The method for preparing the lithium zirconium chloride solid electrolyte according to claim 1, characterized in that: The method also includes the step of grinding the lithium zirconium chloride solid electrolyte into powder, wherein the grinding is performed in a dry inert atmosphere.
9. A lithium zirconium chloride solid electrolyte prepared by the preparation method according to any one of claims 1 to 8.
10. The lithium zirconium chloride solid electrolyte according to claim 9, characterized in that The chemical formula of lithium zirconium chloride is Li x ZrCl 5+x , where x<1.
Citation Information
Patent Citations
Preparation of nanostructured mixed lithium zirconium oxides by spray pyrolysis
CN114364638A
Preparation method of solid electrolyte lithium zirconium chloride
CN114436326A
Lithium secondary battery negative electrode member and its manufacturing method
JP2004220906A
Lithium sulfide, method for producing the lithium sulfide, and method for producing inorganic solid electrolyte
JP2013075816A
